Traditional Religion and Socio-Anthropological Factors Sustaining Widowhood Configurations of Violence on Nigerian Women - Iheanacho, Ngozi N. (Wydawnictwo Naukowe UAM, 2015)
The article is an ethnographic research report in response to Nigerian women’s agitation for advancement and appreciation of their value in the family and society. And also, taking cue from the United Nations clarion call on regular research on customs and traditions that promote women indignities and underdevelopment indices which build up from the family, the paper directs its spotlight on widowhood institution which is characterized by configurations of violence and concomitants of women exploitation and underdevelopment. The practices of the institution are carried out in the pre and post burial phases. They have continued to resist extinction strategies. Not even surrendering to the long struggle and gains of women liberation ideas and policies that abound the world and Nigeria in particular. In the thrust of the report, the paper identifies the sustaining factors of the practices as mainly rooted in traditional religion and socio-anthropological issues, namely: the people’s worldview and concept of sacred phenomenon, the people’s concept of death and ancestorship; the widow’s social and psychological concern for the dead; the people’s idea of marriage and family system; the people’s conformity to the paradigm of myth and sacred history and; the quest for re-union and group cohesion. Among other strategies, formulation of local Christian theologies and legally backed social policies would help to rescue the women from the clutches of the institution.
Keywords: widowhood; women; violence; advancement